(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
It is a well-known fact that family businesses are one of the most important pillars of European Union countries, which includes Croatia as well. However, family businesses more often fail then survive the transfer of business between the generations. Number of Croatian family businesses which are facing this challenge is rapidly growing due to the fact that Croatian companies were mostly established in 1990’s, and the first owners are soon to be retired. The loss of any successful company is an inexcusable loss for the economy and social welfare. Thus, it is an old challenge how to help these companies in transition, whether through transfer between generations of the family or by selling the business. This issue has been acknowledged on the EU level, and there were several studies on the importance and challenges which family business face throughout the EU countries. Also, the EU institutions discussed the possible policies for enhancing the success of family business in transfer, example of which is a Resolution of the European Parliament on family businesses in Europe in 2015. Further, successful transfer of family business is one of the goals in European Commission Entrepreneurship 2020 Action Plan. In this paper, we shall discuss the proposed policies towards family businesses on the EU level, and whether these policies are employed in Croatia. The analysis shall include the EU programs for financing the transition of family business including the option for financing the third person in buying the successful family business. Authors shall assess whether EU policiesadequately address the importance of special governance within these companies. This paper aims to further explore some possibilities for enhancing governance of family businesses which may attribute towards successful transfer of these companies. Also, author shall explore alternative solutions for transfer such as transfer of shares on family foundations which in turn continue managing the family company, but also financially support the family members. It is of particular interest to analyze whether EU policies support introducing new measures on national level which could provide for greater variety of options for entrepreneurs which face the challenge of ensuring the transfer of their business. The conclusion shall be drawn on whether policy for enhancing transfer of family businesses in Croatia is adequate, together with possible options which could be introduced in order to achieve that goal.